Pengaruh Good Corporateigovernance , Whistleblowing System Dan Pengendalian Internal Terhadap Pencegahan//Kecurangan (Fraud) Dalam Lembaga Perkreditan Desa - I Ketut Bagus Demi Ryana Putra; Ni Komang Sumadi; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2024)
This study aims to obtain empirical evidence on the Effect of Good Corporate Governance , Whistleblowing System and Internal Control on Fraud Prevention in village Credit Institutions in Mengwi Badung district. The Mengwi district LPD was chosen in this study because of the phenomenon of fraud that occurred in one of the Mengwi District LPDs. The number of samples taken was 161 respondents. Data collection techniques by observation, interviews, and questionnaires. Multiple linear regression analysis technique is the analysis technique used in this study. It was found that Good Corporate Governance had a positive and significant effect on the variable of accounting (fraud), Whistleblowing System had a positive and significant effect on the variable of accounting (fraud) and Internal Control had a positive and significant effect on accounting (fraud) in the Village Credit Institution Mengwi district. This research can support the fraud triangle theory as a theoretical research implication. It is hoped that this research can provide input to improve Good Corporate Governance, Whistleblowing System, and Internal Control against fraud committed by LPD internal parties with practical research implications. Keywords: Good Corporate Governance, Whistleblowing System, and Internal Control of Fraud Prevention